A new species of Riama Gray, 1858 (Squamata: Gymnophthalmidae) from the Tropical Andes - Aguirre-Peñafiel, Vanessa; Torres-Carvajal, Omar; Nunes, Pedro M. Sales; Peck, Mika R.; Maddock, Simon T. (Zootaxa, 2014)
A new species of Riama lizard from the western slopes of the Andes in northern Ecuador is described herein. Morphologically, Riama yumborum sp. nov. can be distinguished from all other congenerics by having an incomplete nasoloreal suture and a cylindrical hemipenial body with diagonally orientated flounces on its lateral aspect. Phylogenetic analyses of mitochondrial and nuclear DNA support the monophyly of the new species and its sister taxon relationship with R. labionis, which occurs allopatrically.